A NEW CYCLOPHORID LAND SNAIL FROM NORTH SUMATRA, INDONESIA (MOLLUSCA, GASTROPODA: CYCLOPHORIDAE) - MACHFUD DJAJASASMITA (Treubia, 1988)
Pterocyclus spiroliratus n.sp. a cyclophorid land snail is described from Aceh province, North Sumatra. This second species of the genus described from Sumatra is characterized: by the present of several spiral ribs.